The Impact of Green Marketing on Purchasing Decision of Durable Goods An Empirical Study on Energy Saving Lamps Consumers in Amman, Jordan - Dr. Ayed M. Al Muala (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of this study is to identify the impact of cofactors for green marketing on the purchasing decision of durable goods for the consumers of energy saving lamps in the city of Amman by selecting the independent variable which is green marketing includes (price, safe product, environmental awareness of the consumer, and product quality) .A dependent variable is consumers purchasing decision of durable goods. The study population is a consumer of energy saving lamps in the city of Amman. The research population in this research is all consumers of energy saving lamps in Amman city. The researchers distributed 460 questionnaires of study found that the returned for analysis of 394 respondents. The research results showed that the green marketing dimensions (price, safe product, environmental consumer awareness, and product quality) have significant impact on the consumer decision buying for consumers of energy saving lamps in the city of Amman. The study recommended that the necessity to develop the capabilities and competence of the safe product because it has the lowest contribution on consumer decision buying.